Impact of Temperature and Wetness of Summer Months on Autumn Vegetative Phenological Phases of Selected Species in Fageto‑Quercetum in the Years 2011–2015 - Jana Škvareninová; Darina Babálová; Ján Valach; Zora Snopková (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2017)
The work presents the result of the drought impact on the onset and the development of autumn phenological phases of tree species (Quercus robur L., Carpinus betulus L., Prunus avium L.) in the central part of Slovakia. The selected autumn phenological phases of tree species were observed in the years from 2011 to 2015. From meteorological parameters we examined precipitation, number of tropical days, and their periods from June to August. We revealed distinct differences in air temperature and precipitation between the years, which affected the onset of individual phenological phases. Based on the calculations of the Thornthwaite moisture index and climatic water balance, the year 2014 was wet (except for June) with the shortest periods of tropical days. The extreme drought and the longest 13‑day period of tropical days in the year 2015 shifted leaf colouring of hornbeam and cherry tree by 16 and 22 days earlier and the leaf fall by 5 and 16 days earlier than the average of the period from 2011 to 2015. Oak was the least sensitive to the weather extremes, which was documented by a balanced course of the phenological phases with the lowest variation. The 5‑year‑long average onset of the autumn phenophases of oak and hornbeam was shifted by 1 – 4 days later and of cherry tree by 4 days earlier than the 25‑year‑long average.